Advancing quality in sepsis management: a large-scale programme for improving sepsis recognition and management in the North West region of England. Issue 1114 (7th August 2018) - Nsutebu, Emmanuel Fru; Ibarz-Pavón, Ana Belén; Kanwar, Elizabeth; Prospero, Nancy; French, Neil; McGrath, Conor
Abstract: Objective: To evaluate the impact of a collaborative programme for the early recognition and management of patients admitted with sepsis in the northwest of England. Setting: 14 hospitals in the northwest of England. Intervention: A quality improvement programme (Advancing Quality (AQ) Sepsis) that promoted a sepsis care bundle including time-based recording of early warning scores, documenting systemic inflammatory response syndrome criteria and suspected source of infection, taking of blood cultures, measuring serum lactate levels, administration of intravenous antibiotics, administration of oxygen, fluid resuscitation, measurement of fluid balance and senior review. Main outcome measures: Inpatient mortality, 30-day readmission rates and duration of hospital ≥10 days. Results: Data for 7776 patients were included in this study between 1 July 2014 and 29 December 2015. Participation in the AQ Sepsis programme was associated with a reduction in readmissions within 30 days (OR 0.81 (0.69–0.95)) and hospital stays over 10 days (OR 0.69 (0.60–0.78)). However, there was no reduction in mortality. Administration of a second litre of intravenous fluid within 2 hours, oxygen therapy and review by a senior clinician were associated with increased mortality. Starting a fluid balance chart within 4 hours was the only clinical process measure that did not affect mortality. Taking a blood culture sample, administering antibiotic therapy and measuring serum lactate within 3 hours of hospital arrival were all associated with reduced mortality (OR 0.69 (0.59–0.81), OR 0.77 (0.67–0.89) and OR 0.64 (0.54–0.77), respectively) and shorter hospitalisations (OR 0.58 (0.49–0.69), OR0.81 (0.70–0.94) and OR 0.54 (0.45–0.66), respectively). However, none of these measures had an impact on the risk of readmission to hospital within 30 days. Conclusions: The AQ Sepsis collaborative in northwest of England improved readmission and length of stay for patients admitted with sepsis but did not affect mortality. Further cost-effectiveness evaluation of the programme is needed.